Study of the Inclusion Complexation of β-Cyclodextrin-Chloramphenicol and Determination of its Stability Constant - GHARIB NASERI, NAHID; ASHNAGAR, ALAMDAR; YOUSEFIAN, LALEH (Asian Journal of Chemistry, 2010)
Because of the therapeutical significance of chloramphenicol, in the present work, its complexation with β-cyclodextrin is reported. The stability constant (K) of the complexes is determined by UV-Visible spectroscopy.